Gpr37l1/prosaposin receptor regulates Ptch1 trafficking, Shh production, and cell proliferation in cerebellar primary astrocytes. Issue 4 (17th December 2020) - La Sala, Gina; Di Pietro, Chiara; Matteoni, Rafaele; Bolasco, Giulia; Marazziti, Daniela; Tocchini‐Valentini, Glauco P.
Abstract: Mammalian cerebellar astrocytes critically regulate the differentiation and maturation of neuronal Purkinje cells and granule precursors. The G protein‐coupled receptor 37‐like 1 (Gpr37l1) is expressed by Bergmann astrocytes and interacts with patched 1 (Ptch1) at peri‐ciliary membranes. Cerebellar primary astrocyte cultures from wild‐type and Gpr37l1 null mutant mouse pups were established and studied. Primary cilia were produced by cultures of both genotypes, as well as Ptch1 and smoothened (Smo) components of the sonic hedgehog (Shh) mitogenic pathway. Compared to wild‐type cells, Gpr37l1 −/− astrocytes displayed striking increases in proliferative activity, Ptch1 protein expression and internalization, intracellular cholesterol content, ciliary localization of Smo, as well as a marked production of active Shh. Similar effects were reproduced by treating wild‐type astrocytes with a putative prosaptide ligand of Gpr37l1. These findings indicate that Gpr37l1–Ptch1 interactions specifically regulate Ptch1 internalization and trafficking, with consequent stimulation of Shh production and activation of proliferative signaling. Abstract : Genetic ablation of G protein‐coupled receptor 37‐like 1 results in increased patched 1 expression and internalization. This leads to the intracellular accumulation of cholesterol, with concomitant stimulation of sonic hedgehog (Shh) production and activation of Shh‐induced proliferative signaling.